Relación entre las captaciones y colocaciones del sistema financiero de la región Loreto, periodo 2014 - 2018 - Uribe Gonzales, Ender Luis (2020)
The financial theory indicates that the business of financial institutions lies in intermediation, for which they must ensure that placements are financed by fundraising. The objective of this thesis was to determine the relationship between fundraising and placement of the Loreto region's financial system in the 2014-2018 period. For this, this Quantitative research, Correlational level and Non-Experimental design was carried out. The investigation concludes that there is a positive and statistically significant relationship between the deposits and placements of the financial system in the 2014-2018 period, validated by the Correlation Coefficient that was r = 097528958, close value +1; and the Determination Coefficient that reached R2 = 0.951189765, also close to 1. In this sense, there is a good association between the variables and, in addition, the independent variable (feedback) determines the behavior of the dependent variable (placements). On the other hand, the deposits had a permanent growth year by year, except for the year 2017 where it contracted at -4.24%, with the annual average growth of S /. 1,067,123,204 (8.37% annual). In the same way, the placements had an increasing behavior in general terms during the whole series, being the annual average amount of S /. 2,095,270.3.18 (6.69% annual). The average annual late payment was 9.63%, much higher than 5%, raised as a study hypothesis